2022
DOI: 10.1007/s10198-022-01494-2
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of metabolic surgery for the treatment of type 2 diabetes and obesity: a systematic review of economic evaluations

Abstract: Aim To systematically identify and appraise the international literature on the cost-effectiveness of metabolic surgery for the treatment of comorbid type 2 diabetes (T2D) and obesity. Methods A systematic search was conducted in electronic databases and grey literature sources up to 20 January 2021. Economic evaluations in a T2D population or a subpopulation with T2D were eligible for inclusion. Screening, data extraction, critical appraisal of methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 81 publications
(276 reference statements)
2
6
0
Order By: Relevance
“…To the best of our knowledge this is the first published costeffectiveness analysis of ESG. The finding that ESG is cost effective versus LM alone is broadly consistent with published UK-based economic evaluations of other bariatric procedures for severe obesity which have been consistently shown to be cost effective versus LM with interventional costs partly offset by longer-term cost savings in the management of obesity-related comorbidities [19,50,51]. We have also adapted our cost-effectiveness analysis to reflect the US healthcare setting with similar results (manuscript in development) [52], suggesting that our overall findings are broadly generalisable to other developed countries.…”
Section: Consistency With Other Studiessupporting
confidence: 77%
“…To the best of our knowledge this is the first published costeffectiveness analysis of ESG. The finding that ESG is cost effective versus LM alone is broadly consistent with published UK-based economic evaluations of other bariatric procedures for severe obesity which have been consistently shown to be cost effective versus LM with interventional costs partly offset by longer-term cost savings in the management of obesity-related comorbidities [19,50,51]. We have also adapted our cost-effectiveness analysis to reflect the US healthcare setting with similar results (manuscript in development) [52], suggesting that our overall findings are broadly generalisable to other developed countries.…”
Section: Consistency With Other Studiessupporting
confidence: 77%
“…The use of bariatric‐metabolic surgery with shorter T2DM disease duration would likely lead to reduced patient treatment burden and higher rates of T2DM remission. From the health system perspective, bariatric‐metabolic surgery for people with T2DM and severe obesity has been reported as cost‐effective and may even be cost‐saving over longer time horizons 21,28 …”
Section: Discussionmentioning
confidence: 99%
“…From the health system perspective, bariatricmetabolic surgery for people with T2DM and severe obesity has been reported as cost-effective and may even be cost-saving over longer time horizons. 21,28 Possible reasons why bariatric-metabolic surgery appears to be used only in the later stages of T2DM include obesity stigma in healthcare professionals that could disadvantage people with obesity accessing evidencebased care 29 ; lack of participants 30 and primary care clinicians 31,32 awareness of bariatric-metabolic surgery as a therapeutic option in T2DM, concerns about surgical complications 33 and variation in bariatric surgery commissioning influencing referral rates for surgery. A study of primary care clinicians reported little understanding of the role of bariatric-metabolic surgery despite the wideranging impact obesity has on physical and mental health issues.…”
Section: Associations With the Type Of Bariatric-metabolic Surgery Pr...mentioning
confidence: 99%
“…A bariátriai műtétek költséghatékonyságát a diabetes konzervatív kezelésével összehasonlítva számos elemzés mutatta ki, és ezek többségében a műtétek domináns eljárásnak bizonyultak, tehát úgy tudtak többlet egészségnyereséget elérni, hogy közben költséget takarítottak meg [20,21].…”
Section: Bevezetésunclassified